2016
DOI: 10.1111/afe.12164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tree mortality and parasitoid recoveries on the contiguous western invasion front of emerald ash borer

Abstract: 1 A recent invader to North America, emerald ash borer Agrilus planipennis Fairmaire (Buprestidae), is expanding its western range into new habitats. We examined how site factors affect the emergence and damage caused by this beetle on the western edge of its contiguous population in eastern Wisconsin, U.S.A. We characterized forest structure and quantified signs and symptoms of A. planipennis from 2010 to 2013. 2 We evaluated the potential for establishment of three host-specific parasitic Hymenoptera, releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…As has been observed elsewhere in northern states (Duan et al, 2012a(Duan et al, , 2014(Duan et al, , 2015aJohnson et al, in press), we found little evidence that S. agrili was successfully establishing or dispersing even though this species can parasitize up to 50% of EAB larvae in China (Liu et al, 2003), and some experimental work had suggested that the climate in Maryland might facilitate greater parasitism by this species compared with Michigan (Ulyshen et al, 2011). Given that just three EAB larvae parasitized by S. agrili were found at sites two years post-release, it is perhaps more likely that this parasitism was the result of dispersing from a recent release at a nearby site rather than establishment.…”
Section: Discussionsupporting
confidence: 77%
“…As has been observed elsewhere in northern states (Duan et al, 2012a(Duan et al, , 2014(Duan et al, , 2015aJohnson et al, in press), we found little evidence that S. agrili was successfully establishing or dispersing even though this species can parasitize up to 50% of EAB larvae in China (Liu et al, 2003), and some experimental work had suggested that the climate in Maryland might facilitate greater parasitism by this species compared with Michigan (Ulyshen et al, 2011). Given that just three EAB larvae parasitized by S. agrili were found at sites two years post-release, it is perhaps more likely that this parasitism was the result of dispersing from a recent release at a nearby site rather than establishment.…”
Section: Discussionsupporting
confidence: 77%
“…Although only two of the seven parasitoids identified to species are EAB specialists introduced for biological control, four of the other species are known to attack EAB (Marsh & Strazanac, ; Kula et al , ; Duan et al , , ). Thus, the notable increases in relative abundance of Braconidae, Eupelmidae and Ichnuemonidae by 2014 could suggest that some native parasitoids might be responding numerically to EAB populations, similar to trends in other states (Duan et al , , , ; Hooie et al , ; Johnson et al , ).…”
Section: Discussionmentioning
confidence: 77%
“…This inability to regulate high larval densities was also exhibited by the same braconid wasps in a previous study attacking P. semipunctata in E. globulus Labillardière and E. obliqua L'Héritier logs in eastern Australia (Hanks et al 2001). This response appears to depend on factors altering wasp effectiveness in finding larval hosts which may include use of volatiles to locate borer infested hosts (Johnson et al 2016), acoustic cues and audible mechanisms suggested to be used by wasps to find P. semipunctata larvae feeding on the phloem/sapwood (Joyce et al 2011), surface vibrations from borer larvae feeding (Godfray 1994) as was suggested to be used by these braconid wasps when attacking P. semipunctata (Hanks et al 2001), and intensive searching by other braconid wasps (Richerson & Borden 1972). Also, the increased choice of borer infested hosts, combined with the habit of these wasps to land on logs arbitrarily, rather than to remain in one place (Driessen & Bernstein 1999), may have meant that the braconid wasps were likely dispersing throughout the clearfell site and had moved away from host logs with high neonate densities, rather than increasing their chances of finding more individuals among a few logs.…”
Section: Discussionmentioning
confidence: 56%
“…This response appears to depend on factors altering wasp effectiveness in finding larval hosts which may include use of volatiles to locate borer infested hosts (Johnson et al . 2016), acoustic cues and audible mechanisms suggested to be used by wasps to find P. semipunctata larvae feeding on the phloem/sapwood (Joyce et al . 2011), surface vibrations from borer larvae feeding (Godfray 1994) as was suggested to be used by these braconid wasps when attacking P. semipunctata (Hanks et al .…”
Section: Discussionmentioning
confidence: 99%